Vision Servoing Based on the Density Analysis of Texture Elements. (30th January 2013) - Liu, Xiaomin; Zhu, Feng
We present a novel vision servoing method, which is fit for climbing robots and those in unstructured environments, based on texture analysis. A large textured area is the target for observation. After the definition of texture element distribution density, the relationship between the change of the density at some selected points and the camera pose is deduced. The vision servoing control law, which meets the requirement of Lyapunov stability is designed in this paper. Experiments show the effectiveness of this method.